RESEARCH INTO TRUCK TRANSMISSION TORSION VIBRATIONS IN TERMS OF ITS LONGITUDINAL ACCELERATION - Jovanović, Mikica D (Journal of Applied Engineering Science, 2020)
The development of modern motor vehicles is aimed at improving performance in the field of traction characteristics, economy, safety and ergonomic characteristics of the vehicle. Special attention is paid to passenger comfort. Torsional oscillations in transmission cause longitudinal vibrations of the vehicle, depending on inertial parameters as well as the characteristics of stiffness and damping of transmission. Taking into account the complexity of the problem, it is estimated that it is useful to analyse the impact of the constructive transmission parameters of the freight motor vehicle on the longitudinal (fore and aft) vibrations. For this purpose, the dynamic simulation method was used, and the analysis of the influence of certain constructive parameters on the longitudinal oscillations of the vehicle was performed using the so-called “the sensitivity function ", which will be discussed in more detail below.
Keywords: Vehicle; vibrations; truck; transmission; torsional; oscillators; motor vehicles